Dynamics of Use Of Methods And Teaching Books in TPQ Learning Under The Ring of LP. Ma'arif in Garum, Blitar - Riyadus Sholichin; Ahmad Saifudin; Vina Gayu Buana (Journal of Development Research, 2019)
The purpose of this study is to describe the method, textbook, human Resources or ustadz, and financing applied in TPQ under the auspices of LP Ma'arif in Garum District, Blitar. The research method used is qualitative. The results obtained are the methods used, namely Ottoman and CMSA. This TPQ uses the Ottoman method teaching book which can only be used by TPQ institutions that already have Ustadz worship from the Ustmani founder while the CMSA and Iqra' teaching books can be found in bookstores . Teachers of the Ottoman method must have attended training, and the CMSA method instructors can all teach as long as they can read to write the Qur’an. Funding for institutions that apply the Ottoman method costs more than those using the CMSA method.